2005
DOI: 10.1055/s-2005-873156
|View full text |Cite
|
Sign up to set email alerts
|

The Effect of Risperidone on Metabolite Measures in the Frontal Lobe, Temporal Lobe, and Thalamus in Schizophrenic Patients. A Proton Magnetic Resonance Spectroscopy (1H MRS) Study

Abstract: Our results seem to confirm the influence of risperidone on the brain metabolism, specifically in the region of thalamus.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

11
64
2
1

Year Published

2008
2008
2022
2022

Publication Types

Select...
5
4
1

Relationship

0
10

Authors

Journals

citations
Cited by 71 publications
(78 citation statements)
references
References 32 publications
11
64
2
1
Order By: Relevance
“…This hypothesis is consistent with evidence that (1) drugs used to enhance NMDA receptor function in schizophrenia generally show improvement primarily in negative rather than positive symptoms (Javitt 2006;Tuominen et al 2005), (2) an magnetic resonance spectroscopy study of patients with schizophrenia has shown a correlation of temporal glutamine-glutamate levels with negative symptoms (Szulc et al 2005) and (3) negative symptoms but not positive symptoms in schizophrenic patients are correlated with decreased [ 123 I]CNS-1261 binding in the hippocampus in patients on typical antipsychotics . It should, however, be noted that in all studies to date NMDA agonists have been used only as add-on treatments to conventional antipsychotic drugs and so their potential effect on positive symptoms may have been masked.…”
Section: Ketamine Blood Levels and Psychotic Symptomssupporting
confidence: 68%
“…This hypothesis is consistent with evidence that (1) drugs used to enhance NMDA receptor function in schizophrenia generally show improvement primarily in negative rather than positive symptoms (Javitt 2006;Tuominen et al 2005), (2) an magnetic resonance spectroscopy study of patients with schizophrenia has shown a correlation of temporal glutamine-glutamate levels with negative symptoms (Szulc et al 2005) and (3) negative symptoms but not positive symptoms in schizophrenic patients are correlated with decreased [ 123 I]CNS-1261 binding in the hippocampus in patients on typical antipsychotics . It should, however, be noted that in all studies to date NMDA agonists have been used only as add-on treatments to conventional antipsychotic drugs and so their potential effect on positive symptoms may have been masked.…”
Section: Ketamine Blood Levels and Psychotic Symptomssupporting
confidence: 68%
“…We observed an effect of treatment irrespective of antipsychotic for NAA, Glx and Creatine, but this appears to be caused by higher doses pretreatment with other antipsychotics, as results disappeared after correction for baseline haloperidol equivalents. Other studies have also failed to show an effect of treatment on prefrontal NAA levels with both strong and weak D2 antagonists in recently medicated patients [37][38][39]. It has been reported that NAA did initially not decrease after treatment [34], but eventually did after multiple years [33], although the authors could not confirm whether these effects were specific to antipsychotic exposure.…”
Section: Researchcontrasting
confidence: 47%
“…One magnetic resonance spectroscopy ( 1 H-MRS) study compared a group of untreated, manic PBD patients with a group of stable BD patients treated with risperidone [35]. The ACC glutamate/glutamine (Glx) to creatine ratio (Glx/ Cr) was lower in untreated children relative to those on risperidone.…”
Section: Treatment Studies Using Functional Magnetic Spectroscopymentioning
confidence: 99%